Health-related quality of life in hemoglobinopathies: A systematic review from a global perspective - Rodigari, Francesca; Brugnera, Giorgia; Colombatti, Raffaella (Frontiers in Pediatrics, 2022)
Background Sickle cell disease (SCD) and thalassemia are inherited blood disorders, which can lead to life-threatening events and chronic organ damage. Recent advances in treatments have increased life expectancy, and hemoglobinopathies have become chronic illnesses with social and emotional impairments. Thus, health-related quality of life (HRQOL) assessment has a fundamental role in disease management and treatment, and generic and disease-specific questionnaires are reliable and validated measures to estimate disease burden. The heterogeneous distribution of treatment opportunities worldwide influences physical, social, and emotional disease perception. Objectives To review publications concerning HRQOL for SCD and thalassemia in different areas of the world in order to gather a global perspective of questionnaires used and outcomes evaluated. Methods A systematic review of the literature was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The Medline databases were searched on 29 September 2021. Inclusion criteria were as follows: (1) studies of HRQOL assessment in SCD and thalassemia patients by using the PROMIS, the SF-36, the SCSES, the PedsQL-SCD, the PedsQOL generic core scale, the ASCQ-Me, and the TranQoL; and (2) every article type, including non-English studies. We excluded studies that were not limited to SCD or thalassemia and studies that were not specific to hemoglobinopathies, and not consistent with the topic of HRQOL assessment. We did not include the gray literature. A total of 102 out of 124 articles from PubMed, Cochrane Library, and Google Scholar were eligible for inclusion (66 SCD articles and 36 thalassemia articles). The quality of studies was assessed through Critical Appraisal tools for use in JBI Systematic Reviews. Data extraction was conducted using a standardized data collection form (authors, year and country of publication, study design, age and number of patients, HRQOL questionnaires, questionnaire language, and clinical outcomes). Results The evaluation of HRQOL was conducted on all continents, but differences in the worldwide frequency of HRQOL assessment were observed. HRQOL of SCD patients was less investigated in Europe. HRQOL of thalassemia patients was less investigated in South-East Asia and Africa. Generic HRQOL questionnaires (PROMIS, SF-36, and PedsQL) were frequently adopted, while disease-specific ones (ASCQ-Me, SCSES for SCD, and TranQoL for thalassemia) were less used. Translation into local languages has been often performed. Conclusion Health-related quality of life is a complex outcome that has been increasingly incorporated in clinical research and clinical practice worldwide, although with regional differences. Disease-specific outcomes (pain for SCD and transfusion burden for thalassemia) and healthcare system characteristics, particularly in low-income countries, have an impact on HRQOL and should be considered in healthcare plans.